Effect of Lanthanum Addition on the Microstructure of Mg-4Al Alloy - Moosa, Ahmed A. (Al-Khwarizmi Engineering Journal, 2011)
This research was to determine the effect of rare earth metal (REM) on the as-cast microstructure of Mg-4Al alloy. The rare earth metal used here is Lanthanum to produce Mg-4Al-1.5La alloy. The microstructure was characterized by optical microscopy. The phases of this alloy were identified by X-ray diffraction. The microstructure of Mg-4Al consists of α-Mg and grain boundaries with precipitated phase particles. With the addition of Lanthanum, three distinct phases were identified in the X-ray diffraction patterns of the as cast Mg-4Al-1.5La:  Mg, Al11La3, Al4La. The Mg17Al12 phase was not detected. The addition of Lanthanium increases the hardness and decrease the wear rate of Mg-4Al.